Penerapan Good Corporate Governance : Manfaat Dan Tantangan Serta Kesempatan Bagi Perusahaan Publik Di Indonesia - Dwiridotjahjono, Jojok (Jurnal Administrasi Bisnis, 2009)
Corporate governance is still at the top of the agenda for Indonesia and Asian corpo-rations. The issue of corporate governance arises since economic crisis in Indonesiaand Asian countries. Country factors can play a key role in setting the framework forcorporate governance practices at the individual company level. Given that corpo-rate governance matters regardless of the particular system - the legal and economicframework conditions - investors have shown growing interest in a global bench-mark of good behavior. There persists the belief that good corporate governance canhelp create shareholders value and ensuring that enterprizes only responsibility tosociety is to maximize profits without breaking the law, hence the role of corpo-rate governance is to provide appropriate corporate control. This article elaboratedabout implementation good corporate governance ; benefits, obstacles, challenge andopportunity for Indonesia corporations.Keywords: Good Corporate Governance